The COFCO Group - McFarlan, F. Warren (SAGE knowledge. Cases., 2016)
The melamine-tainted baby formula scandal in 2008 led to a crisis across China's dairy industry and struck China dairy giant Mengniu heavily. The company stock took a nosedive; shares mortgaged to Morgan Stanley were greatly devalued, creating a large margin call. Consequently, a capital shortfall arose as well as the risk of being taken over by a foreign firm. Additionally, in February 2009, Mengniu was hit by the OMP scandal, jeopardizing Mengniu's most profitable products. This case study discusses this topic.